2012
DOI: 10.5142/jgr.2012.36.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Effect of Ginsenoside F2against Glioblastoma Multiforme in Xenograft Model in SD Rats

Abstract: The glioblastoma multiforme (GBM) is the most common malignant brain tumor in adults. Despite combination treatments of radiation and chemotherapy, the survival periods are very short. Therefore, this study was conducted to assess the potential of ginsenoside F2 (F2) to treat GBM. In in vitro experiments with glioblastoma cells U373MG, F2 showed the cytotoxic effect with IC50 of 50 μg/mL through apoptosis, confirmed by DNA condensation and fragmentation. The cell population of cell cycle sub-G1 as indicative o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 15 publications
0
31
0
1
Order By: Relevance
“…Several ginsenosides such as ginsenoside Rg3, Rh2, Re, and F2, have been tested in vitro and in vivo as novel anticancer agents to induce apoptosis and inhibit cell proliferation and metastasis. 22,23 Many molecular mechanisms have been proposed for such anticancer activity, Downloaded by [University of Cambridge] at 17:58 16 June 2016 6 including autophagy regulation. [24][25][26][27] Moreover, autophagy contributes to the neuronal protective effects of ginsenoside Rb1 and compound K. 28,29 However, there is currently no evidence showing a direct connection between autophagy and ginsenoside-induced cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Several ginsenosides such as ginsenoside Rg3, Rh2, Re, and F2, have been tested in vitro and in vivo as novel anticancer agents to induce apoptosis and inhibit cell proliferation and metastasis. 22,23 Many molecular mechanisms have been proposed for such anticancer activity, Downloaded by [University of Cambridge] at 17:58 16 June 2016 6 including autophagy regulation. [24][25][26][27] Moreover, autophagy contributes to the neuronal protective effects of ginsenoside Rb1 and compound K. 28,29 However, there is currently no evidence showing a direct connection between autophagy and ginsenoside-induced cell death.…”
Section: Introductionmentioning
confidence: 99%
“…12,13) Ginsenoside Rb1, precursor of ginsenoside F2, has been reported to prevent apoptosis induced by external stimuli in human keratinocyte cells (HaCaTs) as well as to inhibit activation by DHT. 14,15) However, the effects of ginsenoside F2 on hair loss have not been reported.…”
mentioning
confidence: 99%
“…Currently, chemotherapy has proved to decrease the rate of recurrence and improve overall survival; however, the drug resistance and serious toxic side effects largely reduce therapeutic efficacy and quality of life in patients [2, 3]. In recent years, compounds of natural products have caught wide attention due to their promising anticancer effects and minimal side effects [47]. Therefore, it is very necessary to develop new optimal anticancer agent from natural resource [3].…”
Section: Introductionmentioning
confidence: 99%
“…Exploration of ginsenoside as a new anticarcinogenic agent is of much interest [47]. Structural-function studies showed that the increased antitumor effect is implicated with the decrease of its sugar number [5].…”
Section: Introductionmentioning
confidence: 99%